Reasons why patients referred to diabetes education programmes choose not to attend: a systematic review. Issue 1 (15th April 2016) - Horigan, G.; Davies, M.; Findlay‐White, F.; Chaney, D.; Coates, V.
Abstract: Aims: To identify the reasons why those offered a place on diabetes education programmes declined the opportunity. Background: It is well established that diabetes education is critical to optimum diabetes care; it improves metabolic control, prevents complications, improves quality of life and empowers people to make informed choices to manage their condition. Despite the significant clinical and personal rewards offered by diabetes education, programmes are underused, with a significant proportion of patients choosing not to attend. Methods: A systematic search of the following databases was conducted for the period from 2005–2015: Medline; EMBASE; Scopus; CINAHL; and PsycINFO. Studies that met the inclusion criteria focusing on patient‐reported reasons for non‐attendance at structured diabetes education were selected. Results: A total of 12 studies spanning quantitative and qualitative methodologies were included. The selected studies were published in Europe, USA, Pakistan, Canada and India, with a total sample size of 2260 people. Two broad categories of non‐attender were identified: 1) those who could not attend for logistical, medical or financial reasons (e.g. timing, costs or existing comorbidities) and 2) those who would not attend because they perceived no benefit from doing so, felt they had sufficient knowledge already or had emotional and cultural reasons (e.g. no perceived problem, denial or negative feelings towards education). Diabetes education was declined for many reasons, and the range of expressed reasons was more diverse and complex than anticipated. Conclusion: New and innovative methods of delivering diabetes education are required which address the needs of people with diabetes whilst maintaining quality and efficiency.